Management functions and competitiveness in the Portuguese construction industry - Pires, Brígida (2007)
The construction industry faces a wide range of challenges that ought to be addressed if it is to maintain and, if possible, improve its competitiveness. The key interrelated elements of competitiveness have been the focus of many international research projects and studies. The measurement of this success and the quality of the project’s performance depends on the achievement of the main construction management function objectives, namely time, cost, quality and safety, which are the focal indicators for a healthy and competitive construction sector. However, frequent delays, cost overruns, insufficient quality and lack of safety are symptoms of the lack of competitiveness recognized in most construction projects concluded in the last years in Portugal. As a result a research project has been launched to better understand and clarify the reasons behind die lack of achievements of these management functions that affect the competitiveness of the Portuguese construction industry. Results of the survey obtained so for indicate that the main causes for the lack of achievement of the construction functions are due to design and client responsibilities, inadequate construction management and lack of specific training.